PELAKSANAAN DARING (DALAM JARINGAN) DAN LURING (LUAR JARINGAN) PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) SISWA KELAS X DI SMAN 1 KECAMATAN AKABILURU - Lailatul Fitri; Iswantir M; Charles Charles; Supratman Zakir (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the difficulties of teachers with changing learning processes, namely online and offline learning. The teacher who teaches at SMAN 1 Kec. Akabiluru had difficulty adjusting to covid 19. Another problem faced was that students were not allowed to come to school. Teachers and students only meet on learning media that supports it. Teachers also have difficulty in understanding the character of students and teachers are also not free to convey material to students. And also many of the teachers are not proficient in using related social media to support the learning process. With the offline learning process, it is very helpful for teachers in terms of conveying material to students. The offline learning process can also overcome some obstacles during the online learning process. This type of research is a field research with a qualitative approach, which describes a phenomenon that occurs according to the data in the field. Researchers conducted research at SMAN 1 Kec. Akabiluru, with the key informant being the PAI teacher who teaches in class X and the supporting informant being the Principal of SMAN 1 Kec. Akabiluru, class X students and parents of class X students. In collecting data the researchers used interview and documentation techniques. Meanwhile, in analyzing it, the researcher took several steps, namely selecting data, presenting data and drawing conclusions, to test the credibility and validity of the data, the researcher checked the data that had been obtained from several sources, then selected and presented, categorized which views were the same, different and which were more specific. From the research that has been done, it can be concluded that in the implementation of online and offline learning in the pie subject, class x students at sman 1 kec. Akabiluru is more or less going well. This is evidenced by the full support of the school in facilitating teachers and students in the online and offline learning process. The teacher is also eager to provide material to students even though they experience many obstacles. Students have difficulty in participating in learning because of the pandemic conditions that limit the space for students to move in learning. However, they must continue to follow the learning. This right is also inseparable from parental support at home. Keyword: Online Learning, Offline Learning